Helicobacter pylori infection and its correlates among the patients of peptic perforation and gastric carcinoma - Saha, Subhendu Bikas; Bakshi, Sabyasachi; Mandal, Tapas (International Surgery Journal, 2020)
Background: Presence of H. pylori infection was found associated with peptic perforation and gastric carcinoma. Present study tried to estimate the prevalence of H. pylori infection in those patients and to find out the correlates of H. pylori infection. Methods: After matching the inclusion and exclusion criteria, all cases of diagnosed peptic perforation and gastric carcinoma were taken for this prospective, single center, observational study. Results: Among the study population, gastric carcinoma was found in higher age group; whereas peptic perforation was found in lower age group; male and female ratio was 2:1 in both groups of patient. Laborer and housewives were mostly affected in both cases. Gastric carcinoma was more prevalent in urban residents, opposite was seen in peptic perforation. Most patients in two groups had no previous co-morbid condition. Use of NSAIDs was found in high frequency in both groups. Most of the patients were chronic alcoholic and chronic smoker, and most of them had history of taking spicy foods more than twice in a week. Conclusions: H. pylori infection was found in high frequency in both group of patients, and it was higher in peptic perforation. The study establishes the association of H. pylori with the gastric carcinoma and peptic perforation.